A new species of Passiflora subgenus Astrophea (Passifloraceae) from Northern Peru - Esquerre-Ibañez, Boris; Kuethe, J.r. (Phytotaxa, 2025)
A new species of Passiflora subgenus Astrophea found in the cloud forest of the Cajamarca Department, Northern Peru, is here proposed as a new addition to the Andean Flora: Passiflora rimarachiniorum Esquerre & Kuethe. The new species shares morphological characteristics with P. putumayensis, but can be distinguished by having flowers with pubescence near the base of the androgynophore and the base of the styles (vs. glabrous); filaments of pali that are linear, 1–2 mm long, and pale yellow at apex (vs. narrowly linear, up to ca. 4 mm long, and deep yellow in the upper ½); and a white opercular apex (vs. yellow). Further information regarding its ecology, distribution, phenology and preliminary state of conservation are provided in this manuscript.